ANALYSIS OF VILLAGE ASSET MANAGEMENT REPORTS IN BATUPUTE VILLAGE, SOPPENG RIAJA DISTRICT, BARRU REGENCY - Samsibar Samsibar (Sean Institute, 2023)
This study aims to determine the report on the management of village assets and determine the factors that hinder the management of village assets in Batupute Village, Soppeng Riaja District, Barru Regency by using qualitative descriptive research, the type of data used consists of primary data and secondary data accompanied by data collection techniques, namely observation, interview and documentation. While the data analysis techniques through the stages of data collection, data reduction, data presentation, and drawing conclusions.The results of the research conclusions on the village asset management report in Batupute Village, Soppeng Riaja District, Barru Regency at the planning, procurement, and accountability stages are good. While the stages of administration, reporting, and supervision are not good and the factors that hinder the management of village assets are HR competence, lack of communication, attitude of implementers who have not complied with the rules, expertise of activity managers in responding to changing market conditions.